The Future of Cities and Regions Simulation, Scenario and Visioning, Governance and Scale - Bazzanella, Liliana; Caneparo, Luca.; Corsico, Franco; Roccasalva, Giuseppe; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2012)
This guide for tomorrow$1 (Bs urban practitioner systematically explains fifteen best practices across three continents; it explores questions of broad interest for designing and planning the future of cities and regions. Key questions addressed are: Is simulation useful to explore the effects of different design, policy and planning strategies? Which approach will help manage the uncertainties of metropolitan areas both today and tomorrow ? What are the strengths and weaknesses of the different simulation practices for city leadership, public and private partnership, and citizen involvement? The book reviews computer models and media, socio-political initiatives, professional practices which help communicating the future effects of different design, political and planning strategies with a wide range of aims: from information, through consultation, towards active participation. These world best practices are considered according to four leading issues for urban and regional development, respectively Simulation, Scenario and Visioning, Government and Governance, and Scale. The book examines the approaches adopted technically and procedurally. The selected knowledge and the innovative tools used in each case study are among the most advanced and up-to-date in the professional and research fields. This volume successfully illustrates these innovative practices and methodologies in a straightforward and accessible way.s
Preface -- 1. The Relevance of Engaging the Future in Planning Practices -- 2. Chicago Metropolis Plans 2020 -- 3. Communities at the Crossroads: Using MetroQuest to Help Communities Create Consensus around a Vision of the Future -- 4. Stockholm 2030 -- 5. GranTorino. Active and Dialogue Making of the Metropolitan City -- 6. luci2, Scenarios, and the Hendricks County, Indiana, USA, Comprehensive Plan -- 7. Application of Albatross for Scenario Development: Future Travel Behavior in an Ageing Population -- 8. The Preparation of the Kona Region Community Development Plan: A Case Study in Visioning and Visualization -- 9. Oil Vulnerability Scenarios and Regional Visioning in Australia: the South East Queensland Regional Plan -- 10. The Bipolar Metropolitan Region Vienna, Bratislava -- 11. Chula Vista Research Project: Integrating Energy Analysis and Planning at the Neighborhood Scale -- 12. Spatial Elaboration of Long Term Economic and Demographic Trends: Future Land Use and Transport in the Netherlands -- 13. Porta Nuova Station, Turin -- 14. Central Station Stockholm -- 15. The Case Yerseke, using Simlandscape in an Area Development Approach -- 16. Lessons Learnt -- Index.
Keywords: Geography; Regional planning; Sustainable development; Human Geography; Geography; Landscape/Regional and Urban Planning; Sustainable Development; Human Geography